Figurative Language of Cinema World in Joko Widodo Speech - Sundari Mayang Albarusyi Sihaloho; Ervina CM Simatupang (English Journal Literacy Utama, 2020)
This research titled Figurative Language in Joko Widodo Speech. The purpose of this research is to analyze and describe the figure of speech in Joko Widodo speech, the types of figurative language and its meaning of his speech. A qualitative method was used to classify and analyze the data. The technique used in collecting the data was searching videos of Joko Widodo speech. The data used Perrine (1963) and Taylors theories (1981: 167) that many types of figurative language that divide into three classifications namely comparison and substitution, representation by substitution, and contrast by the discrepancy. The data was taken from Joko Widodo Speech in Annual Meeting International Monetary Fund-World Bank in Bali, World Economic ASEAN Forum in Hanoi and US-ASEAN Forum. The author found 9 figurative languages in Joko Widodo speech in the international event; there were 7 allusions, 1 metaphor, and 1 assonance. The conclusion of this research, the using of figurative language is an alternative to implied the literal meaning which can attract the readers or listeners attention and evoke their imagination.